Pengaruh Environmental Knowledge, WOM dan Green Marketing Terhadap Purchase Intention Melalui Environmental Attitude Pada Produk Avoskin - Putri, Hanike Fresnalika; Putlia, Grace (Business Management Journal, 2025)
Green products are an important solution in reducing waste and sustaining the environment. In this context, green marketing has appeared as one of the marketing strategies that provide a positive response for various industries in an effort to achieve sustainability. Avoskin, as one of the brands in the beauty industry, has committed to implementing the concept of green beauty by offering environmentally friendly products and building communities that care about the environment. This study obtained data collected from 260 respondents across Indonesia, using a Likert scale and analyzed with SmartPLS3 software. This research is a quantitative study that found that although environmental knowledge does not directly affect purchase intention, environmental attitudes act as a mediator that can strengthen the influence of environmental knowledge on purchase intention. In addition, the results also show that word of mouth communication and green marketing strategies have a significant positive impact on consumer purchase intention. These findings emphasize the importance of building awareness and positive attitudes towards the environment as a key strategy in influencing consumer buying interest in environmentally friendly products. Therefore, companies and green marketing practitioners are advised to prioritize increasing environmental awareness through campaigns that highlight environmental issues, as well as effective communication strategies and WOM to expand their market.